Implikatur Percakapan Film Uwais Al-Qarni: Analisis Pragmatik - Syafrian (Diwan: Jurnal Bahasa dan Sastra Arab, 2022)
This paper examines the conversational implicatures in the Arabic film Uwais al qarni by Akbar Tahvilian. This research is a qualitative descriptive study. This study focuses on discussing the types of conversational implicatures contained in the Uwais al-Qarni film. The data of this study were analyzed based on George Yule's theory of conversational implicature. With the results found from the Uwais Al Qarni film, the special conversation implicatures are 11 data with the form and form of accusation 2 data, request 3 data, ridicule 1 data, rejection 4 data, hyperbolic 1 data. As well as general conversation implicatures 15 data in the form and form of 8 data reports, 3 data requests, 2 data ridicule, 3 data denials. Conversational implicatures on a scale of 1 data in the form and form of reports or informing.